2011
DOI: 10.1038/jcbfm.2011.172
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Fenfluramine Effect on 5-HT1B Receptor Binding of [11C]AZ10419369 using an Equilibrium Approach

Abstract: Assessment of serotonin release in the living brain with positron emission tomography (PET) may have been hampered by the lack of suitable radioligands. We previously reported that fenfluramine caused a dose-dependent reduction in specific binding in monkeys using a classical displacement paradigm with bolus administration of [11 C]AZ10419369. The aim of this study was to confirm our previous findings using an equilibrium approach in monkey. A total of 24 PET measurements were conducted using a bolus infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…We previously demonstrated that the potent serotonin releaser fenfluramine reduced the binding of the 5-HT 1B receptor radioligand [ 11 C]AZ10419369 in non-human primates by up to 50 % (Finnema et al 2010(Finnema et al , 2012, and similar results have been reported by others using the 5-HT 1B receptor radioligand [ 11 C]P943 (Cosgrove et al 2011;Ridler et al 2011) or the 5-HT 1A receptor radioligand [ 11 C]CUMI-101 (Milak et al 2011). The effects of single SSRI doses have also been evaluated in anaesthetized non-human primates (NHPs) in preparation for studies in human.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that the potent serotonin releaser fenfluramine reduced the binding of the 5-HT 1B receptor radioligand [ 11 C]AZ10419369 in non-human primates by up to 50 % (Finnema et al 2010(Finnema et al , 2012, and similar results have been reported by others using the 5-HT 1B receptor radioligand [ 11 C]P943 (Cosgrove et al 2011;Ridler et al 2011) or the 5-HT 1A receptor radioligand [ 11 C]CUMI-101 (Milak et al 2011). The effects of single SSRI doses have also been evaluated in anaesthetized non-human primates (NHPs) in preparation for studies in human.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-HT 1B receptor functions partly as an autoreceptor (Sari, 2004) and is therefore expected to be sensitive to alterations in endogenous serotonin concentration. Indeed, in non-human primates, [ 11 C]AZ10419369 has proven useful to study regional changes in endogenous serotonin concentration after administration of the serotonin-releasing compound, fenfluramine (Finnema et al, 2010(Finnema et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The application of PET to measure changes in serotonin levels has been hampered by a lack of suitable radioligands (Paterson et al, 2010). There are promising results with the recently developed 5-HT 1B receptor antagonist [ 11 C]AZ10419369, with decreased binding in response to pharmacologically induced serotonin release (Finnema et al, 2012) and high doses of a selective serotonin reuptake inhibitor (SSRI) in nonhuman primates (Nord et al, 2013). However, the effect of baseline serotonin levels on [ 11 C]AZ10419369 binding in humans has not yet been studied.…”
mentioning
confidence: 99%